1990
DOI: 10.1002/1097-0142(19900401)65:7<1626::aid-cncr2820650729>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibrohistiocytic proliferation simulating sarcoma in children

Abstract: The term "inflammatory myofibrohistiocytic proliferation" (IMP) has been proposed to replace the conventional designations of plasma cell granuloma and inflammatory pseudotumor. Three cases of extrapulmonary IMP in children are reported, including an intracerebral lesion which has been formerly undescribed. In children, IMP may be associated with microcytic hypochromic anemia, hypergammaglobulinemia, and high erythrocyte sedimentation rate. In this clinical setting, differentiation of a rapidly growing but ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 25 publications
2
65
0
6
Order By: Relevance
“…IMT and IgG4SD are both fibro-inflammatory proliferations that are included in the larger constellation 6,7 Inflammatory myofibroblastic tumor originates anywhere in the body, but has a predilection for the abdominal cavity, pelvis, retroperitoneum, lungs, mediastinum, and upper respiratory tract. [14][15][16][17]24 In contrast to IMT, IgG4SD is an inflammatory disorder that is accompanied by an elevated serum IgG4 and is histologically characterized by an infiltrative inflammatory fibro-sclerosing process that usually contains abundant IgG4 positive plasma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMT and IgG4SD are both fibro-inflammatory proliferations that are included in the larger constellation 6,7 Inflammatory myofibroblastic tumor originates anywhere in the body, but has a predilection for the abdominal cavity, pelvis, retroperitoneum, lungs, mediastinum, and upper respiratory tract. [14][15][16][17]24 In contrast to IMT, IgG4SD is an inflammatory disorder that is accompanied by an elevated serum IgG4 and is histologically characterized by an infiltrative inflammatory fibro-sclerosing process that usually contains abundant IgG4 positive plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…6 A reported 15-30% of patients have a clinical and laboratory syndrome of fever, malaise, weight loss, anemia, elevated erythrocyte sedimentation rate, thrombocytosis, polyclonal hypergammaglobulinemia, and other inflammatory marker elevations. [7][8][9][10][11][12][13] IgG4-related sclerosing disease (IgG4SD) is a steroid-responsive multiorgan system disorder that encompasses a spectrum of clinical conditions, includ ing autoimmune pancreatitis, sclerosing cholangitis, chronic sclerosing sialadenitis, tubulointerstitial nephritis, cutaneous pseudolymphoma, and sclerosing processes in the lung and pleura, liver, breast, and meninges. 5,[14][15][16][17] The histological findings of fibrosis and chronic inflammation are relatively nonspecific, and there are no known unique genetic markers.…”
mentioning
confidence: 99%
“…Clinical and pathological findings from a review of 13 cases of gastric IMT in children that has been reported under a variety of additional descriptive terms are summarized in Table 1 (4,(8)(9)(10)(11)(12)(13)(14)(15)(16). Most cases were of less than 6-yr-old children (92.3%) and females (69.2%).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] These terms are often confused with soft tissue sarcoma because of its recurrence tendency and local invasion. 5 Main stay of treatment is surgical resection and in some corticosteroids or NSAIDS may be useful. 6 …”
Section: Introductionmentioning
confidence: 99%